AFFECTING FACTORS OF FOREIGN DIRECT INVESTMENT: EXPORT AND GROSS DOMESTIC EXPENDITURE ON RESEARCH AND DEVELOPMENT IN HUMAN CAPITAL CONCEPT (A Study In Indonesia Period 2009-2016) - Shelvia Shelvia; Sri Sulasmiyati (Fakultas Ilmu Administrasi Universitas Brawijaya, 2017)
Penelitian ini bertujuan untuk menghubungkan benang merah antara pertumbuhan ekonomi, investasi asing langsung, ekpor dan pengeluaran pemerintah dalam penelitian dan pengembangan dalam hubungannya dengan konsep human capital. Perbandinngan berdasarkan data dari kegiatan ekonomi di Asia dan Indonesia bertujuan untuk melihat lebih jauh terhadap bukti yang lebih lengkap, perspektif yang lebih luas dan interpretasi yang lebih tepat. Pada penelitian ini menggunakan analisis regresi linear berganda dengan tehnik OLS. Data yang ada berfokus pada variabel ekspor, pengeluaran pemerintah dalam penelitian dan pengembangan dan investasi asing langsung termasuk berbagai ulasan dan bukti pendukung. Hasil dari penelitian diharapkan memiliki implementasi secara praktik terhadap kegiatan ekonomi dan pengembangan human capital. Ekspor sebagai subtitusi dari produktivitas dan pengeluaran pemerintah dalam penelitian dan pengembangan sebagai subtitusi dari progres ilmu dan teknologi di Indonesia akan dijabarkan dalam konsep human capital. Kata kunci: Ekspor, investasi asing langsung, pengeluaran domestik dalam penelitian dan pengembangan, human capital ABSTRACT This study attempts to relate the linkage between economic growth, foreign direct investment (FDI), and between export and gross domestic expenditure on research and development (GERD) in representing human capital. The comparison based on the data of the economy activities in Asia and Indonesia is used to see further a more wide evidence, perpective and the exact interpretation of the test result. This study is using multiple regression analysis to find evidence to prove the hyphothesis with Ordinary Least Square (OLS) techniques. The data is focusing to the relation of FDI, export and GERD variables in particular and including supportive reviews and evidence. The result of this study is expected to have the practical implementation to the economy and human capital enhancement activities. Export as subtitution of productivity and GERD as subtitution of science and technological progress in Indonesia explained in human capital concept. Keywords: Export, foreign direct investment, gross domestic expenditure on research and development, human capital